1980
DOI: 10.1037/0021-9010.65.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Long-term auditory memory: Speaker identification.

Abstract: While working on a cover task, 120 female college students overheard a taped female voice from an adjoining room answer a phone and talk in an angry tone for approximately 11 sec. On a test for speaker identification, subjects listened to tape recordings of the target speaker and four female speakers used as foils, all repeating the original message. The target speaker was presented talking in the original hostile tone or talking in a more normal conversational tone. Two of the distractor voices were hostile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
4
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 12 publications
12
87
4
1
Order By: Relevance
“…The results of this study provide the strongest indication yet of a decline in performance when emotional tone changed, irrespective of whether the emotional tone was presented at study (EN) or at test (NE). Consequently, these data confirmed the findings of Saslove and Yarmey (1980) and Read and Craik (1995) and suggested that emotional voices did not produce the levels of performance associated with 'strong' voices, especially when emotional tone changed from one instance to the next.…”
Section: The Influence Of Vocal Emotion On Voice Processingsupporting
confidence: 78%
See 1 more Smart Citation
“…The results of this study provide the strongest indication yet of a decline in performance when emotional tone changed, irrespective of whether the emotional tone was presented at study (EN) or at test (NE). Consequently, these data confirmed the findings of Saslove and Yarmey (1980) and Read and Craik (1995) and suggested that emotional voices did not produce the levels of performance associated with 'strong' voices, especially when emotional tone changed from one instance to the next.…”
Section: The Influence Of Vocal Emotion On Voice Processingsupporting
confidence: 78%
“…However, surprisingly, the results tend to run counter to expectation. For example, Saslove and Yarmey (1980) conducted a voice line-up task. At the initial study phase, participants overheard an angry speaker for 11 seconds.…”
Section: The Influence Of Vocal Emotion On Voice Processingmentioning
confidence: 99%
“…M e r 2 weeks, accuracy 4 1 dropped to 48%, then to 47% afier 4 weeks and 45% afier 8 weeks. Saslove and Yarmey (1980) looked at shorter delay intervals. The listeners were initially asked to Iisten to a voice sample that lasted 10 seconds and then were asked to atternpt to identify that voice tiom a total of 4 voices, played one at a time.…”
Section: Develo~ment Of Recomition Abilitiesmentioning
confidence: 99%
“…The forensic implications of speaker identification under extreme emotional conditions have long been a motivation for research (Saslove and Yarmey, 1980). A significant number of these studies date before many of the recent advancements in speaker recognition.…”
Section: Introductionmentioning
confidence: 99%